Teenage relationships and sex education. Issue 8 (August 1988) - Curtis, H A; Tripp, J H; Lawrence, C; Clarke, W L
Abstract : Most of the consequences of early intercourse affect the woman and much research has focused upon her. As part of a study on teenage pregnancy, where 137 women were interviewed, 46 men were also interviewed. They were less likely to have had teaching about sex from parents and were subject to less parental supervision than the women. Both sexes had had similar experience of school sex education. Just under half of the men started having intercourse before 16 years. Over half of both sexes were initiated by an experienced partner and for 15/25 (60%) of the men this was within the first month of a relationship. Most men had had several partners and 27/99 (27%) of teenage women at least three, most in the context of stable relationships. 'Serial monogamy' exposes each partner indirectly to their partners previous partners (with the associated medical risks). Education must help teenagers make decisions about sexual involvement that take account of these facts and the implications for their own future health and happiness.